Human trafficking: beyond the borders into India - Sarkar, Siddhartha (Safety and risk in society, 2020)
"Human trafficking remains a pressing global challenge which is a source of enormous misery and abuse. In addition to the human security consequences, trafficking also drives broader problems related to organised crime and underground economy. This book represents one of the first comprehensive evidence-based research projects on human trafficking in a region of the world where sex trafficking thrives. The book has been meticulously put together and may serve as a required resource for police authorities, non-governmental organizations and other public entities that are committed to protecting women and children from this most dreadful form of human exploitation"--